PERLAWANAN PEREMPUAN TERHADAP KETIDAKADILAN GENDER (Semiotika Film “Yuni”) - Pembayun, Jaduk Gilang; Afrilia, Ascharisa Mettasatya (Universitas Teuku Umar, 2023)
Gender issues and discrimination against women are widely found in indonesian society. The presence of films that raise stories and issues about gender is proof that in the midst of the community these problems and phenomena are true. The film Yuni (2021) by director Kamila Andini is one of the films that raises the theme of gender and women's problems that often occur in the community. Yuni's film presents a story inspired by a true story where a teenage girl has to face a difficult time in her school days because the culture encountered in the middle of her environment seems to glorify early marriage. This study aims to find forms of female resistance in Yuni's film. This research was conducted by conducting sign analysis using the semiotic theory of Roland Barthes. The research method used in this study is a qualitative research method with a qualitative descriptive approach. The results of this study found that there are at least three forms of female resistance in Yuni's film that are relevant to the liberal feminism movement and radical feminism. The form of female resistance in question is women's resistance in choosing to continue their education, then women's resistance in determining their own soul mate or partner, and women's resistance to the right in the form of women's freedom in reproductive life and the right to virginity.